2012
DOI: 10.1109/tit.2011.2173613
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Unequal Error Protection Using Multiplexed Hierarchical Modulation

Abstract: With progressive image or scalable video encoders, as more bits are received, the source can be reconstructed with progressively better quality. These progressive codes have gradual differences of importance in their bitstreams, which necessitates multiple levels of unequal error protection (UEP). One practical method of achieving UEP is based on a constellation of nonuniformly spaced signal points, or hierarchical constellations. However, hierarchical modulation can achieve only a limited number of UEP levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 29 publications
1
39
0
2
Order By: Relevance
“…Considering the real-time traffic situation, the proposed method is first theoretically optimized and the achievable performance gain is analyzed. To apply the proposed method into practice, hierarchical quadrature amplitude modulation (HQAM) [18] is employed to implement our SCM-based broadcast scheme. Although HQAM has been used in digital video broadcasting [19], its usage in VANET context is different from the former because of the relatively small single-hop-transmission coverage and time-varying QoS requirements.…”
Section: Improving the Channel Utilization Of Basic Safety Message Inmentioning
confidence: 99%
“…Considering the real-time traffic situation, the proposed method is first theoretically optimized and the achievable performance gain is analyzed. To apply the proposed method into practice, hierarchical quadrature amplitude modulation (HQAM) [18] is employed to implement our SCM-based broadcast scheme. Although HQAM has been used in digital video broadcasting [19], its usage in VANET context is different from the former because of the relatively small single-hop-transmission coverage and time-varying QoS requirements.…”
Section: Improving the Channel Utilization Of Basic Safety Message Inmentioning
confidence: 99%
“…In [5], it was demonstrated that prioritized QAM constellation mapping has a positive impact on the error performance of Turbo Codes by using the UEP characteristics of the QAM constellation where the systematic information bits are given a higher protection. A robust transmission of H.264/AVC coded video using hierarchical QAM (HQAM) was presented in [6]. The non-uniformly distributed importance of frames as well as the sensitivity of the coded bitstream against transmission error were taken into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Hence unequal error protection (UEP) is proposed to make the best use of the bandwidth. A practical approach to achieving UEP is based on modulation, for example, Seok-Ho Chang proposed a multilevel UEP system using multiplexed hierarchical quadrature amplitude modulation (QAM) [1]. Another way to achieve UEP is through channel coding with different coding rates.…”
Section: Introductionmentioning
confidence: 99%